Vanishing Sands Losing Beaches to Mining - Pilkey, Orrin H. (Duke University Press, 2023)
In a time of accelerating sea level rise and increasingly intensifying storms, the world's sandy beaches and dunes have never been more crucial to protecting coastal environments. Yet, in order to meet the demands of large-scale construction projects, sand mining is stripping beaches and dunes, destroying environments, and exploiting labor in the process. The authors of Vanishing Sands track the devastating impact of legal and illegal sand mining over the past twenty years, ranging from Africa, Asia, and the Caribbean to South America and the eastern United States. They show how sand mining has reached crisis levels: beach, dune, and river ecosystems are in danger of being lost forever, while organized crime groups use deadly force to protect their illegal mining operations. Calling for immediate and widespread resistance to sand mining, the authors demonstrate that its cessation is paramount for saving not only beaches, dunes, and associated environments but also lives and tourism economies everywhere.